Developing a Web-based MSME Sales Revenue Data Management and Reporting Portal Using OAuth 2.0 - Setiyawati, Nina; Bangkalang, Dwi Hosanna (Politeknik Harapan Bersama, 2025)
The Cooperatives and SMEs Service (DinKopUKM) under the Ministry of Cooperatives and SMEs play a vital role in coordinating the implementation of tasks, coaching and providing administrative support for MSMEs. In this research, a portal for managing MSME data and Sales Revenue reporting was carried out to support transparent information management, monitoring MSME business implementation, and encouraging orderly administration in MSMEs so as to optimize efforts to empower MSMEs. The portal was developed using Laravel technology for the backend and NextJS for the frontend, with a responsive web design so that it can be accessed from various devices. Apart from that, to support data integration and data communication with resources that have been built in previous research, OAuth 2.0 was implemented. The development process is in accordance with the Prototyping process model. The portal developed was tested using the black box testing method. It was found that this portal was in accordance with the needs and design of the system. The portal developed helps DinKopUKM in carrying out its duties of data collection on MSMEs, monitoring MSMEs, and encouraging MSMEs to maintain orderly administration